Vibration Feedback Controlled by Intuitive Pressing in Virtual Reality - Wang, Yu-Wei; Pan, Tse-Yu; Chang, Yung-Ju; Hu, Min-Chun (My University, 2019)
To provide more immersive experience in VR, highfidelity vibrotactile feedback is one of the most important task to make VR user can feel virtual objects. In this work, we propose a mobile-based vibrotactile feedback system called FingerVIP, which provides an intuitive and efficient way for VR application/game designers to input proper vibration configuration of each target vibrotactile feedback. Our system uses pressure sensors attached on fingers as the controllers to manipulate the vibration configuration, including amplitude, frequency, and time duration. We utilized the proposed FingerVIP to set three kinds of vibrotactile feedback in a VR sports game and validated that FingerVIP successfully helped game designers reduce the number of iteration and the time for configuring vibration.
Keywords: haptic feedback; vibration; pressure; tactile; virtual reality